Magazine for Economic Analysis of Family Duck Raising in Serey Sophorn - Rath, Pisith; Chhay, Kongkea; So, Maly (Journal of Applied Research and Innovation (JARI), 2026)
Family-based agriculture, crop cultivation, and livestock raising, such as ducks, chickens, geese, pigs, cattle, and buffalo, are extremely important for rural populations in Cambodia. These activities contribute to improving household livelihoods, reducing rural poverty, and strengthening food security and the national economy. In particular, family-based duck farming plays a significant role in enhancing household income, supplying food, and supporting national economic development. Family-based duck farming demonstrates strong production capacity and effective management. Market access is convenient, as buyers typically purchase products directly at the farm. Production capital is sourced entirely from farmers’ own funds. On average, a farmer can generate 211,490,000 riels per production cycle. Land productivity yields an income of 2,298,804,300 riels per hectare. Annual depreciation costs amount to 4,544,100 riels, fixed capital costs to 64,557,200 riels, and working capital costs to 89,443,300 riels, resulting in total production costs of 93,987,400 riels. Net profit reaches 328,992,600 riels. The efficiency per unit of production capital is 4.50 riels, fixed capital efficiency is 0.01 riels, and working capital efficiency is 0.21 riels. The break-even point is 14,810 duck eggs at a price of 400 riels per egg. In brief, family-based duck farmers demonstrate prudent and effective business management, enabling them to achieve profitability through efficient investment and appropriate use of labor. Therefore, family-based duck farming can sustainably continue, allowing farmers to recover their investment within one year and achieve maximum profit per production cycle.